1998
DOI: 10.1590/s0102-05361998160000200011
|View full text |Cite
|
Sign up to set email alerts
|

Determinação dos teores de nitrogênio na seiva do tomateiro por meio de medidor portátil

Abstract: O presente estudo objetivou determinar teores e níveis críticos de nitrogênio na forma de nitrato (N-N03) na seiva do pecíolo de tomateiros utilizando-se medidor portátil, e estabelecer a relação destes valores com os teores de N-N03 na matéria seca dos pecíolos, e de N-orgânico e de N-total na matéria seca do limbo. Plantas de tomateiro (Lycopersicon esculentum), cv. Santa Clara, cultivadas em vasos contendo amostras de dois solos (argiloso = Vi; areia-franca = TM), foram submetidas a cinco doses de N (25, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
4
0
7
Order By: Relevance
“…As determinações das formas de N no tomateiro estão detalhadas em Guimarães et al (1998) e, basicamente, constam dos procedimentos listados a seguir.…”
Section: Methodsunclassified
“…As determinações das formas de N no tomateiro estão detalhadas em Guimarães et al (1998) e, basicamente, constam dos procedimentos listados a seguir.…”
Section: Methodsunclassified
“…Kallenbach (2000) found that values of r 2 between concentration of K + in sap and in dry matter of alfalfa leaf was always bellow 0.60 and better correlations were obtained when other variables were taken into account (i.e., leaf moisture, length of the longest stem). Guimarães et al (1998) found a wide range of r 2 values (0.37 to 0.97) when NO 3 -in petiole sap was compared to total-N in leaves of tomato; better results were obtained for leaves located near the first cluster and for sandy soils than for leaves near the third cluster and for clayey soil.…”
Section: Concentrations Of Nomentioning
confidence: 95%
“…Ronchi et al (2001) found r 2 of 0.65 when the N-NO 3 -determined in petiole sap was compared to total-N in leaf dry matter. Locascio et al (1997) cultivated tomato in different locations and verified that the r 2 varied from zero to 0.80, depending on the location and crop age, while Guimarães et al (1998) found r 2 from 0.37 to 0.97 depending on the sampled leaf and soil type. Comparisons of Na + measured in petiole sap and dry matter were not found in the available literature.…”
Section: Concentrations Of Nomentioning
confidence: 99%
See 1 more Smart Citation
“…O correto manejo da fertilização nitrogenada na cultura do tomateiro proporciona adequado crescimento das plantas e boas produções em termos de quantidade e qualidade, além de reduzir os custos de produção e os riscos de contaminação do ambiente (GUImARãES et al, 1998;HE et al, 1999;DzIDA;JAROSz, 2005). Entretanto, na prática, o nitrogênio é aplicado no solo, muitas vezes, de forma empírica e em quantidades excessivas, uma vez que nesta cultura os fertilizantes nitrogenados apresentam um custo relativamente baixo quando comparados a outros insumos agrícolas (ANDERSEN et al, 1999b).…”
Section: Introductionunclassified